2021
DOI: 10.3390/app11136167
|View full text |Cite
|
Sign up to set email alerts
|

Development of Prediction Models for Shear Strength of Rockfill Material Using Machine Learning Techniques

Abstract: Supervised machine learning and its algorithms are a developing trend in the prediction of rockfill material (RFM) mechanical properties. This study investigates supervised learning algorithms support vector machine (SVM), random forest (RF), AdaBoost, and k-nearest neighbor (KNN) for the prediction of the RFM shear strength. A total of 165 RFM case studies with 13 key material properties for rockfill characterization have been applied to construct and validate the models. The performance of the SVM, RF, AdaBo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…The sensitivity results of the GPR model were examined using Yang and Zang's approach for determining the impact of input variables on D H . This strategy, which has been used in a number of research [44][45][46][47], is as follows:…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The sensitivity results of the GPR model were examined using Yang and Zang's approach for determining the impact of input variables on D H . This strategy, which has been used in a number of research [44][45][46][47], is as follows:…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…It was accomplished through the use of a trial-and-error strategy. Previous studies show that the shear strength ( ) of RFM is a function of D 10 , D 30 , D 60 , and D 90 , which correspond to the 10%, 30%, 60%, and 90% passing sieve sizes, while UCS min and UCS max (MPa) indicate the minimum and maximum uniaxial compressive strengths (MPa), the FM and GM parameters describe fineness modulus and gradation modulus, respectively, γ is the dry unit weight (kN/m 3 ), σ n is the normal stress (MPa), and R shows the International Society of Rock Mechanics (ISRM) hardness rating [ 27 , 29 ]. As a result, the current study’s GPR models are constructed using these input variables.…”
Section: Data Catalog and Correlation Analysismentioning
confidence: 99%
“…Zhou et al [ 28 ] has recently shown that cubist and random forest regression algorithms are better at predicting RFM shear strength results than ANN and traditional regression models. To predict RFMs’ shear strength, Ahmad et al [ 29 ] used support vector machine, random forest, adaptive boosting, and k-nearest neighbor algorithms. This field, on the other hand, is still being researched and further explored.…”
Section: Introductionmentioning
confidence: 99%
“…A recently developed approach based on data mining techniques has been increasingly employed to resolve real-world problems for the past half-decade, particularly in the field of civil engineering [18][19][20][21][22][23][24][25][26][27][28]. Several practical problems have already been effectively performed using machine learning algorithms, paving the way for new prospects in the construction industry.…”
Section: Introductionmentioning
confidence: 99%